2011
DOI: 10.1002/jor.21408
|View full text |Cite
|
Sign up to set email alerts
|

Decreased SH3BP2 inhibits osteoclast differentiation and function

Abstract: Germline mutations in SH3BP2 gene have been identified in patients with cherubism, a skeletal disorder characterized by excessive osteoclastic bone resorption that is limited to the mandible and maxilla. We previously demonstrated that SH3BP2 overexpression in Raw264.7 cells increased RANKL-induced osteoclastogenesis. Here, we examine the effect of decreased SH3BP2 on osteoclastogenesis. shRNAknockdown of SH3BP2 decreased PLCγ2 phosphorylation and NFATc1 expression, and reduced the expression of osteoclast-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…We found that expression levels of the genes in Sh3bp2 −/− mouse BMMs stimulated with RANKL or TNFα were reduced compared to expression levels in Sh3bp2 +/+ BMMs (Figure B). These results were similar to the previously reported finding that reduced function of SH3BP2 suppresses the expression of osteoclast‐associated genes in RANKL‐induced osteoclastogenesis and support the observation that NF‐ATc1 nuclear localization was decreased in TRAP+ MNCs from Sh3bp2 −/− mice. However, expression levels of the osteoclast‐associated genes were not significantly reduced in response to simultaneous stimulation with RANKL and TNFα (Figure B), the condition under which TRAP+ MNCs from Sh3bp2 −/− mice exhibited a significantly decreased resorption area (Figure C).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We found that expression levels of the genes in Sh3bp2 −/− mouse BMMs stimulated with RANKL or TNFα were reduced compared to expression levels in Sh3bp2 +/+ BMMs (Figure B). These results were similar to the previously reported finding that reduced function of SH3BP2 suppresses the expression of osteoclast‐associated genes in RANKL‐induced osteoclastogenesis and support the observation that NF‐ATc1 nuclear localization was decreased in TRAP+ MNCs from Sh3bp2 −/− mice. However, expression levels of the osteoclast‐associated genes were not significantly reduced in response to simultaneous stimulation with RANKL and TNFα (Figure B), the condition under which TRAP+ MNCs from Sh3bp2 −/− mice exhibited a significantly decreased resorption area (Figure C).…”
Section: Resultssupporting
confidence: 92%
“…We next investigated the mechanism by which lack of SH3BP2 impairs RANKL‐ and TNFα‐induced osteoclastogenesis. Since previous studies have shown that SH3BP2 regulates RANKL‐induced osteoclastogenesis via activation of NF‐ATc1 , which is an essential transcription factor for osteoclastogenesis , we focused on levels of NF‐ATc1 in BMMs. We found that nuclear expression of NF‐ATc1 was decreased in Sh3bp2 −/− mouse BMMs compared to Sh3bp2 +/+ mouse BMMs at 48–72 hours after stimulation with RANKL, TNFα, or the combination of both; this decrease was particularly marked upon stimulation with TNFα alone (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RAW264.7 cells were used here as they are a preosteoclastic cell line. In addition experiments with the RAW264.7 cell line have accurately predicted the effect of SH3BP2 on bone marrow macrophages and the phenotype of knockin and knockout Sh3bp2 mice [1721]. Compared with the promoter-less reporter, the full-length −2,000 SH3BP2p -LUC reporter exhibited a 15-fold increase in luciferase activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RANKL induced a significant increase in Ca 2+ i of extracellular origin, probably as a result of the opening of TRPV-5 calcium channels on the surface of human osteoclasts. Mutant forms of SH3BP2—occuring in patients with cherubism- potentiate RANKL-induced phosphorylation of PI-PLC-γ isoforms, suggesting that SH3BP2, as well as PLC-γ2, are potential targets in the treatment of disorders characterized by excessive osteoclastic development [481,482]. …”
Section: Pi-specific Phospholipase Cmentioning
confidence: 99%